Civil-Military Cooperation in Addressing Water Crisis in Indonesia (Case Study: Discovery of Clean Water Sources by the Republic of Indonesian Defense University) - Navalina, Vania Kirana Fitria; Sumartono, Winda Ayu Puteri (Civil and Military Cooperation Journal, 2025)
The water crisis in Indonesia poses a significant challenge, particularly in rural and arid regions where access to clean water is limited. This study examines the critical role of civil-military cooperation in addressing this crisis, focusing on a case study involving the Indonesian Defense University. The collaboration between civil authorities and the military led to the successful discovery and management of new clean water sources, demonstrating the effectiveness of combined efforts in resource management. Utilizing a mixed-methods approach, this research highlights the logistical and strategic advantages brought by military involvement, such as rapid mobilization and advanced technological capabilities, in conjunction with civilian expertise in water resource management. The findings underscore the importance of integrated efforts in tackling complex environmental issues and suggest a model for future initiatives aimed at enhancing water security in Indonesia. This case study provides valuable insights into the benefits and challenges of civil-military cooperation, offering practical recommendations for policymakers and stakeholders involved in water management and disaster response.